Stakeholders' different perspectives of critical success and risk factors in a case of large-scale system implementation across Africa - Caren Scheepers; Paul Whelpton (South African Journal of Business Management, 2018)
Background: Most large information technology (IT) projects fail, costing businesses billions of rand while delivering limited benefits. This has stimulated considerable, yet inconclusive, research into the reasons for project success and failure. Objectives: The study explores a massive IT system implementation project, throughout Africa, that cost the organisation almost four times its annual profits and taken more than 10 years. The majority of South African and other African companies in the financial services sector still run on old legacy IT systems and will have to undergo similar exercises. The conceptual model of critical success factors presented here could be used as a high-level blueprint for these future large information system implementations. Method: The research questions required in-depth exploration of circumstances and incidents during the project life cycle and the case study method was the most appropriate design. Thirteen stakeholders were interviewed in a semi-structured interview format. Results: This exploratory case study delivers a comprehensive conceptual model that covers the high-level phases of successful large IT project delivery. It shows that project success only occurs when all critical tasks across the effectiveness and efficiency dimensions of a project are planned, performed and measured accurately. Conclusion: The differences in perspectives between stakeholder groups in the project ecosystem are highlighted, as well as their consequences. The study also contributes to the existing literature by providing a comprehensive formula for the accurate identification of overall project risk.
Keywords: 650